Android Technology in Interactive Learning for Multimedia Animation Courses - Devega, Army Trilidia; Herasmus, Hilda; Sabtu, Sabtu; Ambiyar, Ambiyar; Lapisa, Remon; Larisang, Larisang (invotek, 2024)
Interactive learning media is a tool used to deliver learning content by presenting concepts in an engaging manner that can stimulate interest and participation in learning activities to achieve objectives. This study aims to design interactive learning media for the multimedia animation course, making the learning media more varied and enabling students to learn independently. In designing this android-based interactive multimedia, the researcher used adobe flash with the multimedia development life cycle (MDLC) method, which consists of six stages: concept, design, material collecting, assembly, testing, and distribution. The design results in an android-based interactive multimedia application that provides learning and information about the multimedia animation course, including the semester learning plan for the multimedia animation course, teaching materials, practice questions, and multimedia videos. This product has been validated by two validators: a media expert validator and a material expert validator. The media validity assessment score by the media expert validator is 97% (valid), and the material validity assessment score by the material expert validator is 91% (valid), resulting in an overall average score of 0.94, which is considered valid and suitable for use. The practicality test of the developed learning media was conducted with multimedia lecturers, resulting in a score of 98% (very practical), and with Informatics Engineering Students at Ibn Sina University, specializing in multimedia, with 20 participants achieving a score of 90.77% (very practical). The overall average score is 94%, indicating that the media is very practical. Therefore, it can be concluded that the android-based learning media for the multimedia animation course at Ibn Sina University is highly valid and very practical.